WPSII-8 Forage yield, pasture quality and economic performance after pasture rejuvenation in an organic beef cattle farm. (7th December 2018) - Omokanye, T; Yoder, C; Sreekumar, L; Vihvelin, L; Benoit, M
Abstract: Beef cattle production on productive pastures can be very profitable, but over time, pastures decline in productivity. The following methods of rejuvenation were investigated from 2015–2017 on an organic beef cattle farm: sub-soiling, break & re-seeding, a combination of manure application plus subsoiling, high stock density grazing, bale grazing, pasture rest, as well as direct seeding in spring and fall. Measurements of pasture dry matter (DM) yield and quality were made to determine the most effective and profitable rejuvenation methods in comparison to a complete break and reseeding scenario. The top 3 forage DM yielders were bale grazing, followed by manure application plus subsoiling and then break & re-seeding methods in that order. Overall, all rejuvenation methods investigated produced 5 - 100% higher forage DM yield than control. Of the 15 forage nutritive value parameters measured, only 3 (forage CP, Ca and P) were significantly affected by rejuvenation methods later in the study. Other nutritive value parameters were similar for all methods of rejuvenation investigated including control. Compared to control, the economic analysis showed that the highest input cost was from break and re-seeding. However, when the cost of the hay used for feeding cows for bale grazing was factored into the input costs, then bale grazing would by far have the highest total variable cost/ha. The returns were higher for bale grazing and high stock density grazing than other methods including control. Without having to break and re-seeding old pastures, the 3 top suggested methods of pasture rejuvenation that are expected to reduce time for rejuvenation and loss of pasture productivity, are bale grazing, manure application plus sub-soiling and high stock density grazing.